Preface: Palaeozoic geodynamics of the southwestern margin of Gondwana: controls on the present architecture of the Argentine-Chilean Andes - Colombo, F.; García-Sansegundo, J.; Heredia, N. (Journal of Iberian Geology, 2014)
Palaeozoic geodynamics of the southwestern margin of Gondwana: controls on the present architecture of the Argentine-Chilean Andes